Ultralong SrLi2Ti6O14 nanowires composed of single-crystalline nanoparticles: Promising candidates for high-power lithium ions batteries. (April 2015) - Li, Hongsen; Shen, Laifa; Ding, Bing; Pang, Gang; Dou, Hui; Zhang, Xiaogang
Abstract: To deploy Li-ion batteries for large scale application, it is essential to develop durable electrodes with high power and energy density. Here, we demonstrate that ultralong SrLi2 Ti6 O14 nanowires anode materials synthesized by a simple electrospinning technique are capable of excellent high-rate performance with long stability. The SrLi2 Ti6 O14 nanowires composed of single-crystalline nanoparticles possess the features of "nano-bead-chain" architecture. Used as anode material for lithium ions batteries, the novel SrLi2 Ti6 O14 nanowires exhibits a high reversible capacity of 171.4 mA h g −1 at 0.1 C and retains 96.2 mA h g −1 even at high rate of 20 C. In addition, the capacity is able to stabilize at 101 mA h g −1 after 1000 cycles, corresponding to 0.0086% capacity fading per cycle. Importantly, the Li-storage mechanism of Li2 SrTi6 O14 was revealed by X-ray photoelectron spectroscopy (XPS) and X-ray absorption near edge structure (XANES). The greatly improved electrochemical performance arises from the favorable kinetics properties stemming from unique nanoparticle-in-nanowire one-dimensional architecture. Graphical abstract: Ultralong SrLi2 Ti6 O14 nanowires are reported as a promising candidate for high power lithium ion batteries. The Li-storage mechanism of SrLi2 Ti6 O14 was revealed by X-ray photoelectron spectroscopy (XPS) and X-ray absorption near edge structure (XANES). Owning to the unique "nano-bead-chain" nanoparticle-in-nanowire architecture, the SrLi2 Ti6 O14 nanowires possessing favorable kinetics properties give rise to outstanding electrochemical performances including high capacity, excellent rate capability, high safety, and long lifespan. Highlights: Ultralong SrLi2 Ti6 O14  nanowires composed of single-crystalline nanoparticles. Unique "nano-bead-chain" nanoparticle-in-nanowire architecture. Excellent high-rate performance with long stability. Li-storage mechanism revealed by XPS and XANES.